(untitled) (Baghdad Science Journal, 2025)
The experiment was carried out to study the effect of variety and gibberellic acid in concentration (0 and 50)mg.lat-1 and BL in five concentration (0, 0.50 ,1 ,2 and 3)mg.ltr-1 and their interaction in some chemical Characteristics and total chlorophyll for Dill plant . the experiment designed according Randomized Complete Block Design (RCBD) and three replicates per treatment, compared to the average using less significant difference at the level of probability (0.05) , the results showed the following:- The effect of brassinolide with it,s concentrations led to obtain a significant increase in all the studied characteristics, so the superiority of the concentration of 2 mg.L-1 of brassinolide in each of Ca, Mg,Fe, and total chlorophyll The effect of gibberellic acid with it,s two concentrations led to obtain a significant increase in all the studied characteristics and the highest in of the concentrate at 50 mg.L-1in two local and hol and varieties. The all bilateral interactions had a significant effect on all the studies characteristics with superiority of the treatment (2 from brassinolide, 50 from gibberellic acid) mg. L-1 in the ratio of Ca, Mg,Fe and total chlorophyll. The tripleinter actions led not to obtain a significant increase in all of the study of significant factors